Schools Count : World Bank Project Designs and the Quality of African Primary Education - Heneveld, Ward; Craig, Helen (World Bank, Washington, DC, 2012)
The conceptual framework developed for this study used the review of the literature to identify eighteen key factors that influence student outcomes. The factors are divided into four inter-related categories that are themselves influenced by the institutional, cultural, political, and economic context surrounding the school. Within this context, the supporting inputs flow into each school where interaction among the enabling conditions, school climate, and teaching/learning process combine to produce student outcomes. The report concludes that investment programs for primary education in Africa need to accelerate the trend towards a greater focus on what happens inside schools, towards an even richer package of considerations of what makes education successful at the school level, and towards sectoral policies that empower schools and communities to control better the education of their children. The analysis of the Bank-supported projects leads to two major conclusions. First, the project designs analyzed address an array of inputs that are known to affect educational outcomes: community support, supervision, teacher development, textbooks, and facilities. Second, the project designs tend to ignore the process factors that characterize effective education within schools - school level autonomy, school climate, the teaching/learning process, and pupil evaluation and teacher feedback.